Headache as the sole manifestation of Wilson’s disease - Pathania, Kanika (Indian Journal of Case Reports, 2024)
Wilson’s disease (WD) is an inborn error of copper metabolism caused by a mutation to the copper-transporting gene ATP7B. In the first decade of life, hepatic involvement predominates but neurological manifestations occur in the third or fourth decades. Studies showed Indian children with neuro WD present with behavior abnormality, speech and cognitive impairment, sub-clinical affection of visual pathway, and autonomic function. As a treatable disease, WD should be detected early in the course of the disease by any health professional at any care level, but the rare prevalence of the disease explains the lack of awareness of this disease. Even a high index of suspicion about this entity gets more difficult when the rare and atypical symptom is the only presentation of the disease. Here, we present the case of a 15-year-old girl with worsening headache for the past 3 months as the only neurological manifestation of WD, and that also without any evidence of hepatic involvement.